Penerapan Konsep Zakat Khalifah Umar bin Abdul Aziz - Wardatul Fitriyah (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2022)
Zakat is included in fiqh matters that are important to pay attention to. Umar bin Abdul Aziz RA has a new policy or view on the issue of zakat which includes the policy on assets that are the object of zakat, the mechanism for withdrawing and collecting zakat carried out by the Amilins, as well as the problem of distributing zakat to Mustahiq. The object of zakat becomes expanded because it does not only collect zakat from camels, cows, goats, gold, silver, dates, grains, wheat, but also from employee salaries, lost treasures that are recovered, several types of agricultural and fishery products. For the management and collection of zakat, Umar chose a tsiqah (trusted) and trustworthy amil. The amil also records those who have tithe. Umar also always ensured the legitimacy of each people with their zakat. Meanwhile, in managing the distribution of zakat funds, Umar bin Abdul Aziz applied the policy of al-Shafi'i's opinion. Zakat is given to eight asnaf. One part for the poor, one part for the poor, for amil, for converts, for riqab, for gharim, fî sabîlillah, and another part for ibnu sabîl.